MICROWAVE IRRADIATION EFFECT ON POLYPHENOL CONTENT AND ANTIOXIDANT ACTIVITY OF BASIL - LUNG, Ildiko; SORAN, Maria-Loredana; OPRIŞ, Ocsana; STAN, Manuela Cristina; BELE, Constantin (Studia Universitatis Babeș-Bolyai Chemia, 2018)
This study investigates the influence of microwave field derived from wireless router and mobile telephony sources on polyphenol content and antioxidant activity of basil. The total phenolic content of basil extracts was determined by the Folin-Ciocalteu method. The amount of polyphenolic compounds in basil plants exposed to microwave irradiation was higher compared to control plants. Extracts of irradiated basil exhibit higher antioxidant activity than extracts of control plants, as evidenced by the three methods of determination used: 2,2-diphenylpicrylhydrazyl radical scavenging activity, oxygen radical absorbance capacity and Trolox equivalent antioxidant capacity assays. It was determined that microwave irradiation increased both antioxidant activity and polyphenol content of basil extracts. In addition, hydroalcoholic extracts obtained from basil plants exposed to GSM microwaves showed higher antioxidant activity than hydroalcoholic extracts of plants exposed to WLAN microwaves.